Hypopharynx in termites: Morphological and functional aspects - Silva, Iago Bueno da [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Elsevier, 2017)
The hypopharynx morphology in workers, pseudergates, and soldiers was described in six families of Isoptera using scanning electronic microscopy. This is the first comparative study to detail the hypopharynx among different species of termites, and included 4 one-piece type (OP) and 9 multiple-pieces type termites (MP). The results showed different arrangements of the hypopharynx trichomes, with fewer of these structures in the frontal region of the hypopharynx in pseudergates and soldiers of OP termites. These characteristics did not apply to Serritermes serrifer, since its pseudergates displayed a large quantity of trichomes on the frontal surface. This species may not resemble other OP termites because it does not live inside a piece of wood, but rather are inquilines inside Cornitermes spp. nests. Similar morphology of this mouthpart was observed in the different species of MP termites, with workers exhibiting many unidirectional trichomes on the frontal surface and soldiers presenting fewer of these trichomes. The morphology of the hypopharynx seems to reflect the lifestyle of these species, because MP termites are able to exploit external water sources. Since different arrangements of hypopharynx trichomes are used for water intake via capillary action, the present data reinforce the soldiers’ dependence on workers to obtain water and food through the process of trophallaxis. Three different types of sensilla were observed on the lateral region of the hypopharynx: chaetica, basiconica and campaniformia. Chaetica act as chemoreceptors, while basiconica and campaniformia are mechanoreceptors, used in feeding and environmental perception. Better understanding of hypopharynx morphology permits the inference of ecological habits among OP and MP termites, and reflects the physiological differences between workers and soldiers.
Keywords: Isoptera; Mouthpart; Scanning microscopy; Sensilla